2023
DOI: 10.21603/2308-4057-2023-1-551
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation of trace elements in vegetables grown in various anthropogenic conditions

Abstract: Hazardous compounds accumulate in plants and animals as a result of anthropogenic impact. Trace elements, such as heavy metals, move up in the system of snow – soil – water – plant – animal. When contaminants accumulate in plants that serve as animal feed, they eventually accumulate in the animals that consume the feed because heavy metals usually enter living organisms via digestive tract, i.e., with food. In 2003–2021, we studied fodder plants grown and harvested by urban zoological organizations, e.g.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The Cr levels in coriander leaves and the shoots of dill were 1.20 mg/kg and 3.40 mg/kg, respectively (Table 1), exceeding the allowable Cr limit reported by the FAO/WHO [4]. In parsley plants, Cr was not detected because a variety of contemporary methods are currently being used to remove heavy elements from soil by phytoremediation, phytodetoxification, soil rinsing, and leaching [19]. The Cu content in coriander varied between 7.40 and 11.30 mg/kg, with variation of 10.50 to 14.80 mg/kg in parsley, 0.70 to 1.30 mg/kg in dill, and no Cu detected in arugula (Table 1).…”
Section: Levels Of Trace Elements In the Studied Samplesmentioning
confidence: 83%
See 2 more Smart Citations
“…The Cr levels in coriander leaves and the shoots of dill were 1.20 mg/kg and 3.40 mg/kg, respectively (Table 1), exceeding the allowable Cr limit reported by the FAO/WHO [4]. In parsley plants, Cr was not detected because a variety of contemporary methods are currently being used to remove heavy elements from soil by phytoremediation, phytodetoxification, soil rinsing, and leaching [19]. The Cu content in coriander varied between 7.40 and 11.30 mg/kg, with variation of 10.50 to 14.80 mg/kg in parsley, 0.70 to 1.30 mg/kg in dill, and no Cu detected in arugula (Table 1).…”
Section: Levels Of Trace Elements In the Studied Samplesmentioning
confidence: 83%
“…Another study revealed that the TF values of Pb 2+ , Fe 2+ , and Cu 2+ were higher than those of Ni 2+ and Zn 2+ , leading to the conclusion that Ni 2+ and Zn 2+ ions have a restrictive effect on internal transport in crops [69]. The amount of accumulation of Zn, Cu, and Fe in edible vegetables is contingent on the concentration of their water-soluble metal forms in the soil [19]. The TF water-plant summarized in Table 3 indicate that Fe has an effect on plants through transfer from water, which is an essential element found in most living things.…”
Section: Transfer Factor (Tf)mentioning
confidence: 99%
See 1 more Smart Citation
“…Industrial enterprises have a negative impact on ecosystems if they do not have good wastewater treatment systems [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%